Pengaruh Lokasi, Persepsi Harga dan Citra Merek Terhadap Keputusan Pembelian di Toko Daging Nusantara Kranggan - Amelia Rinjani; Salman Paludi (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
The purpose of this study to examine how the influence of location, price perception and brand image on consumer purchasing decisions at Toko Daging Nusantara Kranggan. This survey was conducted on consumers who purchased Toko Daging Nusantara products during April-May 2023. In this study using quantitative methods. The primary data of this study was collected through questionnaires using the accidential sampling method, with a total of 100 respondents. The collected data is then tested for validity and reliability. Data analysis involved multiple linear regression analysis, correlation coefficients and determination coefficients using SPSS software version 25. The findings of this study show that price perception and brand image have a partial influence on purchasing decisions. However, locations have no partial influence on purchasing decisions. Overall, the study's findings suggest that these three variables simultaneously influence purchasing decision.